2007
DOI: 10.1097/01.bpb.0000236236.49646.03
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications of supracondylar humeral fractures in children

Abstract: The purpose of this study was to analyze the vascular complications of 24 children with supracondylar humeral fractures treated in two affiliated hospitals and to propose a management plan. Exploration and repair of the brachial artery were undertaken in 11 of the 24 cases in which the pulse did not resume following reduction of the fracture. The repaired vessels were found to be patent on follow-up. Angiography was performed in six of the 24 cases and resulted in improved management in comparison with cases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 20 publications
4
78
0
3
Order By: Relevance
“…Postoperative establishment of continuous anterior humeral and coronoid lines shows the success of surgical treatment. The percent and number of vascular complications was similar to the literature data (17,18). Myositis ossificans is an indicator of damaged soft tissue around the elbow and is associated with poorer functional outcomes.…”
Section: Resultssupporting
confidence: 73%
“…Postoperative establishment of continuous anterior humeral and coronoid lines shows the success of surgical treatment. The percent and number of vascular complications was similar to the literature data (17,18). Myositis ossificans is an indicator of damaged soft tissue around the elbow and is associated with poorer functional outcomes.…”
Section: Resultssupporting
confidence: 73%
“…Copley et al [6] reported that a formal angiography should be performed before surgery if either the pulseless limb has no clinical signs of severe ischaemia and the essence or location of the vascular injury remains unknown due to previous vascular pathology or combined limb trauma, or when a surgical exploration is being debated. Furthermore, intra-operative arteriography with the aid of a C-arm is a useful tool in cases in which the radial pulse is not palpable after an attempt of fracture reduction [15]. The same authors hold that the only contraindications for intraoperative arteriography are Gustilo type I and II open fractures, as well as severe ischaemia of the limb [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intra-operative arteriography with the aid of a C-arm is a useful tool in cases in which the radial pulse is not palpable after an attempt of fracture reduction [15]. The same authors hold that the only contraindications for intraoperative arteriography are Gustilo type I and II open fractures, as well as severe ischaemia of the limb [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations